Hands-On Cloud Development with WildFly - Tomasz Adamski (Packt Publishing, 2018)
"Hands-On Cloud Development with WildFly" guides you through building, deploying, and managing cloud-based enterprise Java applications using technologies like WildFly Swarm and OpenShift. This practical guide covers everything from microservices creation to cloud deployment and production-grade readiness, equipping you with skills to build and deploy scalable, reliable applications.What this Book will help me doMaster the usage of WildFly Swarm to create and optimize Java-based microservices.Implement cloud deployments and container orchestration with OpenShift.Utilize Jenkins for implementing CI/CD pipelines to automate your application lifecycle.Secure enterprise applications using advanced technologies such as Keycloak.Enhance application resilience and performance by integrating Hystrix.Author(s)Tomasz Adamski is a seasoned software developer and architect with vast experience in Java and cloud applications. He has spent years designing and implementing enterprise Java systems, making him an authority on this subject. Tomasz's educational and approachable teaching style makes learning complex topics engaging and actionable.Who is it for?This book is ideal for experienced Java developers aiming to extend their expertise into cloud-based development. Whether you're familiar with basic Java EE applications or seeking to harness the cloud's full potential for enterprise-grade systems, this step-by-step guide will meet your needs. It is particularly tailored for professionals interested in using WildFly Swarm and OpenShift for microservices in the cloud.